(untitled) (Research, Society and Development, 2020)
Excessive sodium consumption is a worldwide public health problem. The big challenge is to make reductions in sodium content without affecting the physical and technological characteristics and the sensory acceptance of food. The objective of this study was to evaluate the influence of the addition of potassium chloride and enzymatic preparation with transglutaminase on the physical characteristics of cracker with reduced sodium content. The control sample contained only sodium chloride (1.81% w/w), from which 10 other formulations were prepared, reducing the sodium chloride content and adding potassium chloride and enzymatic preparation (from 0 to 1.80% w/w). The mass (g), thickness (cm) and length (cm) of the crackers were measured before and after baking. The loss of mass (g), specific volume (cm³.g-1) and instrumental texture (hardness and fracturability) of the crackers were also evaluated after baking. After baking, the thickness of all crackers increased numerically. The fracturability value was lower than the hardness value for all treatments, demonstrating that the crackers were not brittle. For most of the formulations, the substitution of sodium chloride for potassium chloride and enzymatic preparation resulted in an increase in the values of the length, the hardness and the fracturability of the baked cracker; and reduction in the values of specific volume and loss of mass when baking. Therefore, the reduction of sodium chloride and the addition of potassium chloride and enzyme preparation altered the technological characteristics of crackers.